Fenomena Perluasan Makna dalam Interaksi Penutur Bahasa Indonesia di Media Sosial X (Januari—Juli 2024): Analisis Semantik - Wahyu Laksono; Endang Nurhayati (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
This study aims to see language change in the form of meaning expansion between Indonesian speakers on social media X in the period January to July 2024. This qualitative research uses the method of listening and recording to collect data from the interaction of Indonesian speakers. The results of this study show that there are 11 data found to have experienced changes in the meaning of language in the expansion of meaning. The most frequently found causal factors are social and cultural change factors, then previous meaning associations and differences in areas of use. The three causal factors for the expansion of meaning with each data are as follows: 1) association factors totaling 3 data, namely in the words